Influence of a high intensity intermittent training program on VO2MAX, body fat percentage and muscular endurance in high school students. (Revista horizonte, 2014)
Objective: the purpose of this study was intended to determine the effects of a high-intensity interval training (HIIT) program by considering variables of maximum oxygen consumption (VO2 max), body fat percentage and muscular endurance on secondary school students. Methods: 23 subjects (n=23) were chosen on this quasi- experimental study; (fourteen women and nine men) from a semi-private school in Paillaco. vo2mAX was measured by Course Navette test, body fat percentage by using bioelectrical impedance and performance on endurance tests of squats, crunches and push-ups. Then, 24 sessions of HIIT were developed twice a week and the pre and post results were compared over the mentioned variables by using the Student's t-distribution statistic (SPSS V18). RESULTS: With a 24 sessions HIIT program, a significant improvement (p